#### Answer

the graph is in the picture.

#### Work Step by Step

if $t\lt-1$ then $h(t)=-t-t-1=-2t-1$
if $-1\leq t \lt0$ then $h(t)=-t+t+1=1$
if $t \geq0$ then $h(t)=t+t+1=2t+1$
and the graph is in the picture.

Published by
Cengage

ISBN 10:
1285740629

ISBN 13:
978-1-28574-062-1

the graph is in the picture.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.